Volatiles, color characteristics and other physico–chemical parameters of commercial Moroccan honeys. Issue 3 (1st February 2016) - Petretto, Giacomo Luigi; Tuberoso, Carlo Ignazio G.; Vlahopoulou, Gina; Atzei, Alessandro; Mannu, Alberto; Zrira, Saadia; Pintore, Giorgio
Abstract : Seven commercial Moroccan honeys were considered for chemical characterisation. Volatile fraction, total polyphenols content, antioxidant and antiradical activities were evaluated by employing different analytical methodologies. Several physical parameters such as refractive index, pH, water content, solids content and colour were measured. Volatile fraction revealed an abundant presence of cis- and trans- linalool oxide in the seven studied samples. The presence of high levels of compounds related to the Maillard reaction, like furfural and hydroxymethylfurfural, could be the result of thermal treatments used to liquefy commercial honeys or of long storage times. The CIE L * a * b * C ab * h ab ° chromatic coordinates confirmed the advanced stage of the Maillard reaction, showing L * values lower than the common values found for honey of similar typologies. Abstract :